Gene expression atlas of fruit ripening and transcriptome assembly from RNA-seq data in octoploid strawberry (Fragaria × ananassa). Issue 1 (December 2017) - Sánchez-Sevilla, José; Vallarino, José; Osorio, Sonia; Bombarely, Aureliano; Posé, David; Merchante, Catharina; Botella, Miguel; Amaya, Iraida; Valpuesta, Victoriano
Abstract RNA-seq has been used to perform global expression analysis of the achene and the receptacle at four stages of fruit ripening, and of the roots and leaves of strawberry (Fragaria × ananassa ). About 967 million reads and 191 Gb of sequence were produced, using Illumina sequencing. Mapping the reads in the related genome of the wild diploidFragaria vesca revealed differences between the achene and receptacle development program, and reinforced the role played by ethylene in the ripening receptacle. For the strawberry transcriptome assembly, ade novo strategy was followed, generating separate assemblies for each of the ten tissues and stages sampled. The Trinity program was used for these assemblies, resulting in over 1.4 M isoforms. Filtering by a threshold of 0.3 FPKM, and doing Blastx (E-value < 1 e-30) against the UniProt database of plants reduced the number to 472, 476 isoforms. Their assembly with the MIRA program (90% homology) resulted in 26, 087 contigs. From these, 91.34 percent showed high homology toFragaria vesca genes and 87.30 percentFragaria iinumae (BlastN E-value < 1 e-100). Mapping back the reads on the MIRA contigs identified polymorphisms at nucleotide level, using FREEBAYES, as well as estimate their relative abundance in each sample.